THE EFFECT OF FICUS CARICA ON LEAD ACETATE INDUCED CHANGES IN THE HEIGHT OF GERMINAL EPITHELIUM OF SEMINIFEROUS TUBULES OF ADULT RAT TESTES - Ayesha Asad (Army Medical College Rawalpindi, 2019)
Objective: To evaluate the effect of Ficus carica on lead acetate induced changes in the height of germinal epithelium of seminiferous tubules in testes of adult rats.